Ethnomathematics Exploration Through Traditional Madurese Games in Elementary School Mathematics Learning - Zayyadi, Moh.; Misriyana, Septiyadini; Ratnadi, Dewi (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This research aims to determine the principles of ethnomathematics in elementary school mathematics learning through traditional Madurese games and what mathematical concepts are contained in traditional Madurese games. The traditional games referred to in this research are engklek (bhisek), hide and seek (rem-ngerreman), and ball bekel (bal bleken). This research uses qualitative research with an ethnographic approach. The instrument in this research is a human instrument, the researcher is directly related to the research and acts as a data collector through library data collection, interviews, observation and documentation. Data analysis techniques are carried out by data reduction, data presentation, data analysis, and data exposure. The results of this research are ethnomathematics principles in traditional Madurese games which can be seen from the preparation before playing, how to play and the rules of the game. Mathematical concepts contained in the game engklek (bhisek): the concepts of addition and subtraction, numbers, lines and angles, flat shapes, and comparisons, in the game hide and seek (rem-ngerreman): the concepts of addition and subtraction, and numbers, and in bekel ball game (bal bleken): concepts of addition and subtraction, number patterns, multiplication and division and comparison